2008
DOI: 10.1007/s10162-008-0119-x
|View full text |Cite
|
Sign up to set email alerts
|

Transplantation of Mouse Embryonic Stem Cells into the Cochlea of an Auditory-Neuropathy Animal Model: Effects of Timing after Injury

Abstract: Application of ouabain to the round window membrane of the gerbil selectively induces the death of most spiral ganglion neurons and thus provides an excellent model for investigating the survival and differentiation of embryonic stem cells (ESCs) introduced into the inner ear. In this study, mouse ESCs were pretreated with a neural-induction protocol and transplanted into Rosenthal's canal (RC), perilymph, or endolymph of Mongolian gerbils either 1-3 days (early post-injury transplant group) or 7 days or longe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
79
0
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 78 publications
(88 citation statements)
references
References 79 publications
(63 reference statements)
5
79
0
2
Order By: Relevance
“…However, ouabain did not damage the morphology of the cochlear hair cells. These results demonstrate that the local npg administration of ouabain successfully induced the AN model in gerbils in this study, which is consistent with previous studies [17][18][19] .…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…However, ouabain did not damage the morphology of the cochlear hair cells. These results demonstrate that the local npg administration of ouabain successfully induced the AN model in gerbils in this study, which is consistent with previous studies [17][18][19] .…”
Section: Discussionsupporting
confidence: 93%
“…Following application of ouabain into the round window (RW) niche of gerbil, the animals showed relatively normal otoacoustic emissions and cochlear microphonics in conjunction with increased thresholds for cochlear whole-nerve action potentials (CAPs) and ABRs [17][18][19] . The ouabain-induced AN model has been shown to selectively and permanently destroy most spiral ganglion neurons (SGNs) with little effect on the morphology and function of the sensory hair cells and the cells in the cochlear lateral wall [17][18][19] . Thus, the ouabain-exposed gerbil is believed to be a reliable model of human AN [17] .…”
Section: Introductionmentioning
confidence: 99%
“…Several prior studies (Schmiedt et al, 2002;Lang et al, 2005;Lang et al, 2008) have shown that ouabain application to the round window area can cause dramatic attenuation of cochlear neural responses, such as the ABR or the compound action potential, without significantly affecting responses that do not require cochlear synaptic transmission, such as the DPOAEs.…”
Section: Cochlear Function Testsmentioning
confidence: 99%
“…One particularly powerful one was first discovered in the gerbil, where repeated application of ouabain to the round window membrane, designed as a means to cause strial atrophy, was instead seen to cause massive degeneration of the type-I spiral ganglion cells innervating the inner hair cells (Schmiedt et al, 2002), without significant loss of hair cells, and with preservation of hair cell function, at least as seen via otoacoustic emissions (Lang et al, 2005;Lang et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation